Identidade social e lógicas institucionais do funcionalismo público - Carvalho, Rúbia Walquiria de (2016)
This study aimed to describe how the employment contracts and their underlying logics constitute the social identity of employees of a federal institution of health, located in Rio de Janeiro. It was employed qualitative study using the data collection tool for carrying out semi-structured interview based on three categories: institutional logic, functions and activities and identities. As for the bureaucratic logic, it was found that it is more common to mid-level employees, regardless of the type of bonds. Already Management Logic is more common among professionals employed by public foundation and civil servants, top-level office holders. It was also possible to conclude that, in relation to self image, the vast majority of respondents see as official standard and value their professional performance. The identification of employees in relation to the other, contracted by private enterprise and contractors by public foundation, see the public server as accommodated, absent and not very responsible, depending on stability. Both hired by a private company as civil servants consider the foundation's employees as experts with vast technical knowledge, valued, high-wage possessors and flexibility. Already civil servants and contractors by public foundatio n share the opinion that the employees hired by private enterprise, work by the need to keep their jobs, being seen as "workmen" who act on the basis of coercion, in view of the lack of stability . Regarding the perception of employees hired by private company as they are seen, they think be seen as exemplary employees, belittled by colleagues from other links. As for the employees hired by the public foundation think they are respected by knowledge and viewed with envy by occupy a prominent position without having made a public tender. The servers believe they are seen as responsible employees, who perform their duties with aplomb.